Diagnosis and Prognostic Assessment of Drug-Induced Liver Injury: What Are the Outpatient Options? (Review) - E. V. Gantsgorn; A. V. Bozhko; S. V. Yarchenko (Безопасность и риск фармакотерапии, 2025)
INTRODUCTION. Drug-induced liver injury (DILI) is a common and potentially life-threatening complication associated with the use of medicinal products and bioactive dietary supplements. Recognising early signs of liver damage can be challenging for a number of reasons, including polypharmacy, comorbidity, pre-existing liver conditions, and misinterpretation of non-specific clinical manifestations. It is necessary to consolidate information on the diagnostic and prognostic options for DILI that are available to physicians in outpatient settings.AIM. This study aimed to provide consolidated and systematised information on the risk factors, early diagnosis methods, and prognostic assessment methods for DILI to provide recommendations for DILI identification in outpatient settings.DISCUSSION. The main risk factors that contribute to the development of DILI are potentially hepatotoxic medicinal products, high doses of medicinal products, polypharmacy, a history of liver disease, and genetic predisposition. Even though DILI can occur with any medicinal product, outpatient physicians should be aware of the medicinal products that are most often associated with this condition. The initial screening for liver injury and the determination of its severity necessitate taking a comprehensive medication history and conducting standard liver function tests (alanine transaminase, aspartate transaminase, alkaline phosphatase, total bilirubin). Tools relevant for outpatient care include scales that help identify the cause-and-effect relationship between a medicinal product and liver damage. These include the Council for International Organisations of Medical Sciences/Roussel Uclaf Causality Assessment Method (CIOMS/RUCAM) scale, the Maria & Victorino scale (M&V), the Digestive Disease Week–Japan (DDW–J) scale, the Naranjo Adverse Drug Reaction Probability Scale). The CIOMS/RUCAM scale is suitable for suspected hepatocellular or cholestatic DILI, and the M&V scale is additionally adapted for mixed DILI and includes points for extrahepatic manifestations. Other relevant tools for outpatient care are those for predicting the severity of DILI (Hy’s law).CONCLUSIONS. Outpatient physicians should adopt an approach that combines medication history collection, physical examination, laboratory investigations, and instrument-based diagnostics with the routine use of scales for establishing causality between a medicinal product and DILI. This approach will help predict the clinical course of DILI at an early stage and make a quick decision on further treatment.